COMBINATION OF VCO (Virgin Coconut Oil) AND FISH OIL IN COMMERCIAL FEED ON THE GROWTH AND SURVIVAL OF FRESHWATER POMFRET FISH (Colossoma macropomum) - Riski Saputri Sianipar Mulianda; Suri Purnama Febri; Siti Komariyah (JURNAL AKUAKULTURA, 2025)
Pomfret (Colossoma macropomum) is a freshwater fish that is one of the leading commodities in Indonesia, and has good prospects for development because it has a delicious and savory taste. The obstacle that is often faced today in pomfret cultivation is the high Feeding Rate value in pomfret fish is not comparable to the growth produced by efforts made to increase growth and survival in pomfret fish, namely by adding VCO and fish oil to commercial feed. The research design used in this study was an experimental method using a Completely Randomized Design (CRD) with 4 treatments and 3 replications where P1: 7% Fish oil / kg feed, P2: 5% Fish oil + 2% VCO / kg feed, P3: 3% Fish Oil + 4% VCO / kg feed, and P4: 7% VCO / kg feed. The results obtained on absolute weight growth showed the best treatment, namely in P3, which was 10.46 g, while the best survival rate was in P1, which was 96.67%. In P1, where fish oil is 7% with a survival value of 96.67%, this is because fish oil contains omega-3 fatty acids such as DHA and EPA which are important for increasing the immunity and physiological function of pomfret fish.